Lost customers: determinants and process of relationship dissolution - Lopes, Luisa (2011)
Relationship dynamics and relationship ending have received increased attention by marketing researchers over the last years. The success of businesses depends not only on the acquisition and retention of customers, but also on avoiding their defection. Furthermore, there is a lack of research in the services literature focusing on the decline and ending of customer relationships. By knowing more about the nature, elements, stages and factors involved in the dissolution process it will be easier to prevent churn or regain lost customers. This research presents a literature review about what contributes to and influences this process (switching determinants) suggesting the most and less relevant determinants, according to ample and updated research. This review also provides some preliminary ideas about the process of relationship dissolution that is proposed on the end of the paper.